The band wide manegement for 6G Network - Aggoun khaoula zineb; Ramdani Saadi (Université Amar Thelidji- Laghouat FACULTE: DE TECHNOLOGIE DEPARTEMENT D’ELECTRONIQUE, 2022)
With the launch of the fifth generation of mobile networks with 10 gigabits per second as minimum of data rate using high frequencies than 4G, doors are opened to several services such as the Internet of things, virtual reality and others. However, a demand of more transmitted data and low latency is needed. In order to answer all that, a new release of mobile network is under study, called beyond 5G (b5G) or 6G. The main tool that is expected to be used for increasing the throughput is the terahertz frequencies band wide for new physical layer. That will guide us to create a new technic for the huge band wide manegement, which was not needed in the precedent generations. In the simulation done, we tried to modify the cell number and user’s number to observe the sum-rate evolution. For deducing the parameters that could manage the new physical layer under study.
OPTION : Réseaux et Télécommunications